A PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN ALAT PERAGA KOTA GEOMETRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR KELAS IV SDN MANYARAN 01 KOTA SEMARANG SEMESTER II TAHUN PELAJARAN 2023/2024: - - Nur Cholis Nur Cholis; Ika Ratnaningrum; Ika Susanti (STKIP Subang, 2024)
The problem in this research is the low learning outcomes in mathematics in class IV of SDN Manyaran 01. After observations were made, the cause of the low learning outcomes was the use of learning models and demonstration media that were still conventional in nature. This encourages researchers to apply the problem based learning (PBL) learning model assisted by geometric city teaching aids. The purpose of this research is to determine the improvement in the results and process of learning mathematics about flat shapes in class IV students at SDN Manyaran 01, Semarang City. This type of research is classroom action research. The data source used is quantitative data in the form of test data on student learning outcomes which are analyzed using quantitative and qualitative descriptive techniques. The data collection technique in this research is to use observation and tests. Meanwhile, the data collection tool in this research used teacher and student IPKG observation sheets. Based on the research results, the average value of pre-cycle learning outcomes was 69.29, increasing in cycle I from 74.64 to 87.86 in cycle II. Meanwhile, teacher skills in the mathematics learning process also increased, in the pre-cycle it was 64.71, increasing to 72.94 in cycle I and increasing again to 88.24 in cycle II. The results of this research can prove that the problem based learning (PBL) learning model assisted by geometric city teaching aids with flat shapes is effective in improving the learning outcomes of class IV students at SDN Manyaran 01, Semarang City.